2022
DOI: 10.31989/ffs.v2i11.1012
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and Tempus Theories of Functional Food Science: Establishment of dosage and time of consumption of functional food products

Abstract: Over the years the United States has seen an increase in the prevalence of chronic diseases. For that reason, there has also been an increased need in products that can prevent or manage symptoms of disease. Functional food products are food products that contain bioactive compounds that have been shown to produce beneficial effects that increase health. The Functional Food Center has previously a 16-step process to develop functional food products and bring them to the market. As part of this process, researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Probiotics [including those present in "Narineh"] produce bioactive compounds that actively compete with pathogens [67], actively working to help restore the intestinal microbial environment against disease. The quantum and tempus theories of functional food science establish the dosage and duration at which a bioactive compound is effective by preventing or managing symptoms of a disease [68]. The dosage in this…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics [including those present in "Narineh"] produce bioactive compounds that actively compete with pathogens [67], actively working to help restore the intestinal microbial environment against disease. The quantum and tempus theories of functional food science establish the dosage and duration at which a bioactive compound is effective by preventing or managing symptoms of a disease [68]. The dosage in this…”
Section: Discussionmentioning
confidence: 99%
“…Various studies on vitamin D have demonstrated its effectiveness as a means for managing the prevalence of vitamin D deficiency and its role in various health aspects in its biologically active form, 1,25dihydroxyvitamin D3 [1,21,[57][58]. The next two steps necessitate the suitable dosages and optimal timing of consumption of the bioactive compound [60,62]. Based on the studies examined in this review, it is evident that the appropriate dosage of vitamin D varies based on aspects including age, health condition, and vitamin D status.…”
Section: Bioactive Compounds In Health Andmentioning
confidence: 99%
“…The Functional Food Center has contributed to an enhanced definition of functional foods. These foods contain biologically active compounds and provide specific and clinically validated health benefits [184]. The blood-brain barrier (BBB) permeability of these compounds allows them to directly interact with brain cells and exert their beneficial effects.…”
Section: Anti-agingmentioning
confidence: 99%